Educational achievements and export earnings: a comparison between leader and follower countries - Alam, Gazi Mahabubul; Forhad, Md. Abdur Rahman (Emerald, 2023)
Purpose This study examines whether education in developing countries directly impacts their foreign income from the top export sector.